A method for solving nonlinear differential equations: An application to λϕ4 model - Ruy, Danilo V. [UNESP] (L and H Scientific Publishing, 2015)
Recently, it has been great interest in the development of methods for solving nonlinear differential equations directly. Here, it is shown an algorithm based on Padé approximants for solving nonlinear partial differential equations without requiring a one-dimensional reduction. This method is applied to the λϕ4 model in 4 dimensions and new solutions are obtained.
Keywords: Integrable equations in physics; Integrable field theory; Padé approximants; λϕ4 model